The Effectiveness of a Program Based on The Use of Virtual Museum in Developing Tourism Awareness in Early Childhood Stage - Alaradi, Ebtesam Abdulaziz (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to investigate the effectiveness of a program based on the use of the virtual museum in developing tourism awareness during early childhood. The researcher employed a quasi-experimental design with two groups, as it was suitable for the nature of the current research. The sample was divided into two groups: an experimental group and a control group.The researcher developed and used the following tools: the Pictorial Tourism Awareness Scale (prepared by the researcher) and the program based on using the virtual museum to develop tourism awareness during early childhood (prepared by the researcher). These tools were applied to a sample of 60 children in the early childhood stage, with an average age ranging from 4 to 6 years.The results of the current study revealed the effectiveness of the program in enhancing children’s tourism awareness through the use of the virtual museum, as observed in the follow-up measurement of the children in the research sample and confirmed by the results of the study hypotheses.The researcher recommended the importance of designing programs and activities that provide information about tourism in the Kingdom of Saudi Arabia.
Keywords: virtual museum; tourism awareness; early childhood